Visualization of the Goddess Hera Character as a Fantasy Dress with the Saviors Theme - Wahyuni, Siti; Puspitasari, Feny (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2024)
Fantasy dress refers to clothing created through imagination or inspiration, often resembling original objects or ideas. These ideas typically stem from mythical figures such as the Goddess Hera, renowned in Greek mythology as the queen of the goddesses. Hera's regal character inspires fantasy dress designs, aligned with themes like "The Saviors," highlighted in the 2023-2024 Indonesian Fashion Trend Forecast by the Indonesian Fashion Chamber. This research explores how Hera's character can be visualized through fashion design, employing a practice-led research approach. Findings reveal two interpretations: a feminine depiction using soft materials, ruching techniques, and gold accessories, and a masculine portrayal featuring structured capes, sturdy fabrics, and cobalt blue accents. These interpretations illustrate Hera's dual feminine and masculine aspects within the context of "The Saviors" theme in the Indonesian fashion forecast for 2023-2024.